Association Between Work Attendance When Experiencing Fever or Cold Symptoms and Company Characteristics and Socioeconomic Status in the COVID-19 Pandemic in Japanese Workers: A Cross-Sectional Study. Issue 3 (9th March 2022) - Mizuki, Kazuyoshi; Okawara, Makoto; Hino, Ayako; Ando, Hajime; Nagata, Tomohisa; Tateishi, Seiichiro; Tsuji, Mayumi; Matsuda, Shinya; Fujino, Yoshihisa
Abstract : This study showed that a lack of a policy requesting that employees refrain from attending work while ill was associated with attendance at work while experiencing fever or cold symptoms. Thus, such a policy is a beneficial countermeasure for companies to prevent the spread of infection. Abstract : Objective: This study investigated the association between attending work while experiencing fever or cold symptoms and workers' socioeconomic background and company characteristics during the COVID-19 pandemic. Methods: A cross-sectional online survey was performed. Of a total of 33, 302 participants, 3676 workers who experienced fever or cold symptoms after April 2020 were included. The odds ratios (ORs) of attending work while sick associated with workers' socioeconomic background and company characteristics were evaluated using a multilevel logistic model. Results: The OR of attending work while sick associated with a lack of policy prohibiting workers from working when ill was 2.75 (95% CI: 2.28 to 3.20, P  < 0.001). Conclusion: This study suggests that clear company policies on work and illness can be effective for preventing employees from attending work while sick.